Advertising and Promotions in the US Green Industry - Hayk Khachatryan; Alicia Rihn; Marco A. Palma; Charles R. Hall (EDIS, 2014)
US firms that sell nursery and garden products have become more interested in effective advertising and promotion strategies. A major question for these green industry firms is how to stimulate additional sales. This 3-page fact sheet was written by Hayk Khachatryan, Alicia Rihn, Marco A. Palma, and Charles R. Hall, and published by the UF Department of Food and Resource Economics, August 2014.